Scale-up of reverse electrodialysis for energy generation from high concentration salinity gradients - Hulme, Anna; Davey, Christopher J.; Tyrrel, Sean; Pidou, Marc; McAdam, Ewan (Elsevier, 2021)
Whilst reverse electrodialysis (RED) has been extensively characterised for saline gradient energy from seawater/river water (0.5 M/0.02 M), less is known about RED stack design for high concentration salinity gradients (4 M/0.02 M), important to closed loop applications (e.g. thermal-to-electrical, energy storage). This study therefore focuses on the scale-up of RED stacks for high concentration salinity gradients. Higher velocities were required to attain a maximum Open Circuit Voltage (OCV) for 4 M/0.02 M, which gives a measure of the electrochemical potential of the cell. The experimental OCV was also much below the theoretical OCV, due to the greater boundary layer resistance observed, which is distinct from 0.5 M/0.02 M. However, negative net power density (net produced electrical power divided by total membrane area) was demonstrated with 0.5 M/0.02 M for larger stacks using shorter residence times (three stack sizes tested: 10 × 10cm, 10 × 20cm and 10 × 40cm). In contrast, the highest net power density was observed at the shortest residence time for the 4 M/0.02 M concentration gradient, as the increased ionic flux compensated for the pressure drop. Whilst comparable net power densities were determined for the 10 × 10cm and 10 × 40cm stacks using the 4 M/0.02 M concentration gradient, the osmotic and ionic transport mechanisms are distinct. Increasing cell pair number improved maximum current density. This subsequently increased power density, due to the reduction in boundary layer resistance, and may therefore be used to improve thermodynamic efficiency and power density from RED for high concentrations. Although comparable power densities may be achieved for small and large stacks, large stacks maybe preferred for high concentration salinity gradients due to the comparative benefit in thermodynamic efficiency in single pass. The greater current achieved by large stacks may also be complemented by an increase in cell pair number and current density optimisation to increase power density and reduce exergy losses.
Keywords: Salinity gradient energy; Cell pair; Thermal-to-electric; Recycle Battery; Closed-loop